Investigating Acupoint Selection and Combinations of Acupuncture for Tic Disorders: An Association Rule Mining and Network Analysis Study - Chen, Jieting; Xie, Yufeng; Lin, Qingchan; Qian, Ziliang; Feng, Jun; Zhang, Jianmei; Chen, Yun; Chen, Wenhan; Wu, Yueting; Guo, Ziyi (Frontiers in Neurology, 2022)
Objective: A tic disorder (TD) is a common mental disorder in children and adolescents, and the clinical application of acupuncture for treating TDs is becoming increasingly widespread. However, the basic rules for selecting acupoint prescriptions and the combination of acupoints have not been summarized. Therefore, data mining was used in the present study to discover the treatment principles and the most effective acupoint selection and compatibility rules for the acupuncture treatment of TDs. Methods: Clinical studies and clinical efficacy observations of acupuncture treatment for TDs were searched and retrieved from the PubMed, Cochrane Library, EMBASE, China National Knowledge Infrastructure (CNKI), Wanfang, VIP, and Chinese Biomedical (CBM) databases. The data on the acupoint prescriptions applied in these studies were collected, and network and association analyses were used to reveal the relationships between acupoints and to discover hidden acupoint combinations. Additionally, the principles of acupuncture for TDs were determined through cluster analysis. Results: A total of 2100 relevant studies were retrieved, and 257 groups of effective prescriptions were extracted, involving 121 acupoints. Bai-hui (DU20), Feng-chi (GB20), Tai-chong (LR3), He-gu (LI4), and San-yin-jiao (SP6) were the most regularly used acupoints for treating TDs. The Governor Vessel, gallbladder, and large intestine meridians were more commonly used than other meridians. Moreover, the selection sites of acupoints focused on the head and neck. Network analysis revealed potentially effective acupoint prescriptions for their commonly used acupoints, namely, Bai-hui (DU20), Si-shen-cong (EX-HN1), Feng-chi (GB20), Nei-guan (PC6), Shen-men (HT7), He-gu (LI4), Zu-san-li (ST36), San-yin-jiao (SP6) and Tai-chong (LR3). Association rule mining indicated that potential point unions that should be prioritized in TD treatment are Bai-hui (DU20), Neiguan (PC6) and Sanyinjiao (SP6). Cluster analysis revealed the treatment principle of “coordinating yin and yang, tonifying qi and blood, dispelling pathogenic wind and eliminating phlegm”. Conclusion: Based on a data mining analysis of published studies, this study provides valuable information regarding the selection of the most effective acupoints and point combinations for clinical acupuncture practice for treating TDs.